2019
DOI: 10.1002/cne.24656
|View full text |Cite
|
Sign up to set email alerts
|

Functional connectivity changes in core resting state networks are associated with cognitive performance in systemic lupus erythematosus

Abstract: To investigate core resting state networks in SLE patients with and without neuropsychiatric symptoms by examining functional connectivity changes correlating with results of cognitive testing. Structural MRI and resting state‐fMRI (rs‐fMRI) were performed in 61 female SLE patients (mean age: 36.8 years, range 18.2–52.0 years) and 20 healthy controls (HC) (mean age 36.2 years, range 23.3–52.2 years) in conjunction with clinical examination and cognitive testing. Alterations in core resting state networks, not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
15
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 64 publications
5
15
1
Order By: Relevance
“…The prevalence of fatigue ranges from 76% to 100% in active or inactive SLE patients [6264], so we thought fatigue is a common symptom of systemic lupus erythematosus. Previous studies found that patients with SLE had significantly higher scores of FSS compared to healthy controls, which is consistent with our study [12, 6466]. We will carry out relevant researches in the future.…”
Section: Discussionsupporting
confidence: 92%
“…The prevalence of fatigue ranges from 76% to 100% in active or inactive SLE patients [6264], so we thought fatigue is a common symptom of systemic lupus erythematosus. Previous studies found that patients with SLE had significantly higher scores of FSS compared to healthy controls, which is consistent with our study [12, 6466]. We will carry out relevant researches in the future.…”
Section: Discussionsupporting
confidence: 92%
“…SMG is a portion of the inferior parietal lobe ( 37 ), whereas the dorsolateral MFG and IFG mainly belong to the dorsolateral prefrontal cortex ( 43 ). Hyperconnectivity was found between the hippocampus with the inferior parietal lobe, INS, and dorsolateral prefrontal cortex in this study, which parallels the previous research ( 14 ). Integrated research on non-NPSLE patients utilized diffusion tensor imaging, and fluorine-18 fluorodeoxyglucose positron emission tomography approaches found that the patients had compromised microstructural integrity in clusters that contained the HIP, frontal and parietal lobe ( 44 ).…”
Section: Discussionsupporting
confidence: 92%
“…Brain network anomaly has been previously explored in non-NPSLE. Using the independent component analysis method, Nystedt et al ( 14 ) found the increased functional connectivity (FC) within the default mode network (DMN) and central executive network and in-between these two sub-networks in non-NPSLE. Another study detected altered FC within the DMN, salient network, central executive network, and working-memory network ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence to suggest that SLE patients, with and without overt NPSLE, have aberrations in their white matter microstructures as seen by diffusion tensor imaging (DTI) [36]. Functional MRI studies have shown increased functional connectivity in core resting-state networks in SLE patients that correlate with reduced cognitive performance compared with healthy controls [37]. FDG-PET imaging highlighted hypermetabolic regions that corresponded with increased serum anti-NMDAR antibodies in SLE patients with CD and did not correlate with disease duration, activity, medications or comorbidities [26,27].…”
Section: Advanced Imaging Studiesmentioning
confidence: 99%